Densification and microstructure of lead zirconate titanate ceramics fabricated from a triol sol-gel powder - C. Sangsubun (2018)
Lead zirconate titanate (PZT) nano-powder was prepared by a triol sol-gel process. X-ray diffraction and transmission electron microscopy results showed that as-synthesized amorphous powder started to crystallize at the calcination temperature above 500 °C. The crystalline powder was formed into pellets and sintered at temperatures between 900 and 1300 °C. Co-existence of tetragonal and rhombohedral phase was observed in all ceramics. Microstructural investigation of PZT ceramics showed that uniform grain size distribution with average grain size of ∼0.8-2.5 μm were received with sintering temperature up to 1200 °C. Further increasing the temperature caused abnormal grain growth with the grain as large as 13.5 μm. An attempt to optimize densification with uniform grain size distribution was also performed by varying heating rate and holding time during sintering. It was found that dense (∼97%) sol-gel derived PZT ceramic with uniform microstructure was achieved at 1100 °C with a heating rate of 5 °C min-1and 6 h dwell time. © 2007 Elsevier B.V. All rights reserved.